Analisis Faktor Penempatan Jabatan terhadap Prestasi Kerja Karyawan pada PT. Zaman Teknindo Pekanbaru - Muhammad Arif; Bayu Ardiyan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
Humans as labor in company activities have a very important role. The purpose of this study was to determine the effect of the position placement factor on employee performance at PT. Zaman Teknindo Pekanbaru. The types and sources of data used in this study are primary data and secondary data with a total sample of 44 people. Sampling is done using the census method. Whereas to determine the magnitude of the influence of the independent variable (X) on the dependent variable (Y), Simple Regression analysis was used with the help of the Set 17. Package for Social Science (SPSS) device based on the results of the Simple Linear Regression. employee work at PT. Zaman Teknindo Pekanbaru. Thus to obtain high work performance, the management at PT. Zaman Teknindo Pekanbaru needs to pay attention to the application of work placements that are in accordance with what is owned by the employee such as ability, skills and experience and the better the work placement that is set by the company, the better the workplace pays generated by the employee. Keywords: Job Performance, Job Placement